2022
DOI: 10.1021/acs.cgd.2c00861
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Trimorphism in an Ionic Cocrystal of Hesperetin

Abstract: We report the existence of conformational polymorphism in an ionic cocrystal (ICC) of the nutraceutical compound hesperetin (HES) in which its tetraethylammonium (TEA+) salt serves as a coformer. Three polymorphs, HESTEA-α, HESTEA-β and HESTEA-γ, were characterized by single-crystal X-ray diffraction (SCXRD). Each polymorph was found to be sustained by phenol···phenolate supramolecular heterosynthons that self-assemble with phenol···phenol supramolecular homosynthons into C 3 2(7) H-bonded motifs. Conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
2
1
0
Order By: Relevance
“…No cyclic dimers were found between HES molecules. When HES is deprotonated, the results reported here and in our previous study on polymorphic ICCs of HES with its tetraethylammonium salt (Jin, Haskins et al, 2022) reveal that HES À anions may form infinite chains with (in HESTEA-) or without (in HESTEA-, HESTEA-) HES molecules. They may also self-assemble into cyclic dimers which were found in four out of the seven structures reported in this work.…”
Section: Hydrogen-bonding Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…No cyclic dimers were found between HES molecules. When HES is deprotonated, the results reported here and in our previous study on polymorphic ICCs of HES with its tetraethylammonium salt (Jin, Haskins et al, 2022) reveal that HES À anions may form infinite chains with (in HESTEA-) or without (in HESTEA-, HESTEA-) HES molecules. They may also self-assemble into cyclic dimers which were found in four out of the seven structures reported in this work.…”
Section: Hydrogen-bonding Analysissupporting
confidence: 58%
“…It has been suggested that symmetric [PhOÁ Á ÁHÁ Á ÁPhO] À hydrogen bonds can be classified as quasicovalent bonds in nature due to incomplete proton transfer (Steiner, 2002). The [PhOÁ Á ÁHÁ Á ÁPhO] À hydrogen bonds observed in HESNAH [2.4618 (18) A ˚] and HESKHEÁ2H 2 O [2.451 (2) A ˚], reported here, HESTEA-[2.4256 (19) A ˚] reported by us recently (Jin, Haskins et al, 2022), and bis(4-Nitrophenoxide) dihydrate [2.434 (6) A ˚] reported by Kreevoy et al (1998), are shorter than other PhOHÁ Á ÁPhO À hydrogen bonds [2.479 (3) A ˚to 2.660 (3) A ˚] observed in this work.…”
Section: Hydrogen-bonding Analysissupporting
confidence: 57%
“…44 However, as the number of reports on polymorphic cocrystals continues to rise, most of these reports focus on structural characterization. [45][46][47][48][49] Solubility studies, on the other hand, are still relatively scarce. Upon examining the available data, it becomes clear that the BZMDSLC and BZMDFMA polymorphic cocrystals can serve as representative examples for many of the other reported cases.…”
Section: Solubilitymentioning
confidence: 99%